Determination of the margin for error when dismounting from the asymmetric bars - Hiley, M. J.; Yeadon, M. R. (International Journal of Computer Science in Sport, 2002)
The margin for error when releasing the A-bars may be quantified in terms of the timing error for which the gymnast has suitable linear and angular momentum for performing the required dismount. If the gymnast releases with less error than this she will have sufficient linear and angular momentum to complete the dismount. A computer simulation model of a gymnast on the asymmetric bars is used to determine the margin for error of dismounts performed at the Sydney Olympic Games.